Application of multi-teaching model based on the hospital-school joint teaching in the practical training of nursing students in the intensive care unit (基于院校联合的多元教学模式在ICU护生临床实习教学中的应用研究) - MA Minrong (马敏蓉); WU Zhiqun (吴志群); CHEN Lan (陈岚); DENG Qiongfang (邓琼芳); GUO Lin (郭琳); LI Yunhui (李云辉) (中西医结合护理)
Objective To explore the effect of the multi-teaching mode based on the hospital-school joint teaching in the practical training of nursing students in the intensive care unit(ICU). Methods Totally 93 nursing students were trained using multi-teaching mode based on the hospital-school joint teaching, and the training and teaching effect were evaluated. Results After training, the operation evaluation results of simple respiratory balloon, artificial airway sputum suction, ECG monitoring, oral care, central venous pressure measurement, ventilator tube installation and parameter setting of ICU nursing students were improved(P＜0. 05). The operation score of simple respiratory balloon of nursing students from vocational school was superior to that of undergraduate students (P＜0. 05), and there was no significant difference in the rest of operation evaluation results (P>0. 05). The satisfaction of nursing students with teaching was high. Conclusion The multi-teaching mode based on the hospital-school joint teaching can improve the practical operation ability of nursing students in ICU, enhance the ability to adapt to ICU, improve the teaching quality, and help to cultivate practical nursing talents suitable for the development of the times. (目的 探究基于院校联合的多元教学模式在ICU护生临床带教中的应用效果。方法 对 2019 年7月—2020年1月在医院ICU实习的护生93人进行基于院校联合的多元教学模式培训, 并评价培训及教学效果。结果 培训后, ICU护生简易呼吸气囊的使用、人工气道吸痰、心电监护、口腔护理、中心静脉压测量以及呼吸机管路安装及参数设置等操作考核成绩均有较培训前提高, 差异有统计学意义(P＜0. 05), 且专科生在培训后简易呼吸气囊的使用操作得分优于本科生(P>0. 05), 其余操作考核成绩本科生与专科生的差异无统计学意义(P>0. 05)。护生对于带教满意度较高。结论 基于院校联合的多元教学模式可提高护生在ICU的实践能力, 增强适应ICU的能力, 提高教学质量, 有利于培养适合时代发展的实用型护理人才。)